The Utilization of the Educational Game ‘Duck Race’ as an Innovative Formative Assessment in Islamic Education Learning at Cahaya Cendekia Elementary School - Sufiyatul Qumariyah; Ainur Rofiq Sofa (Lembaga Penerbitan, Penelitian dan Pengabdian kepada Masyarakat, Institut Badri Mashduqi, 2025)
This study aims to examine the implementation of the educational game “Duck Race” as an innovative formative assessment in Akidah Akhlak learning for Grade II students at Cahaya Cendekia Elementary School. Using a qualitative descriptive approach, the research explored learning practices, classroom interactions, and students’ experiences in a natural setting. Data were collected through classroom observations, in-depth interviews, and documentation involving the principal, vice principal for curriculum, PAI teacher, and selected students. The findings show that the “Duck Race” game was implemented in a structured, interactive manner that promoted active participation and enthusiasm. The game helped transform abstract moral concepts into concrete experiences, improving students’ interest, focus, and understanding. As a formative assessment, it enabled teachers to observe comprehension, moral reasoning, and behavioral responses during learning. Challenges included preparation time, limited facilities, and classroom management. Overall, the study concludes that “Duck Race” is an effective formative assessment strategy. Game-based learning in Islamic education supports meaningful learning and moral internalization effectively.